Aktualisasi Indikator Desa Ramah Perempuan dan Peduli Anak Sebagai Upaya Strategi Pemberdayaan Masyarakat Kelurahan Bulusan - Akhmad Sahlan Zakariya; Divfa Putra Gustionningsih; Hanun ’Aqilatuzzakiyyah; Fatimatuz Zahroh; Inge Alfiyah Damayanti; Novita Ainiyyatuz Zakiyyah; Ainis Salsabil; Fitri Lindayunita (Universitas KH. Mukhtar Syafaat (UIMSYA), 2025)
This study focuses on actualizing the Women-Friendly and Child-Care Village (DRPPA) indicators as a community empowerment strategy in Bulusan Village, Banyuwangi. DRPPA is a government initiative aimed at protecting women and children while promoting gender equality and enhancing women’s roles in entrepreneurship and child-rearing. The research employed the Participatory Action Research (PAR) method, involving the community actively to foster social change. The mentoring program revealed that urgent issues in Bulusan included stunting and limited educational resources for pregnant women. The DRPPA program was implemented with a community-centered approach through regular Posyandu (integrated health post) activities and the “Sentuh Gemilang” initiative, which emphasized nutritional improvement and health education. Results demonstrated increased public awareness and knowledge about the importance of nutrition for children’s development, as well as a higher level of community engagement in empowerment activities. This study concludes that the PAR method is an effective strategy for empowering communities and fostering a village environment that supports women and children.